Corruption Perception Index as a Moderating Variable in the Relationship between Village Funds, Local Revenue, Technology Adoption, and Village Independence in Indonesia - Sudarman; Etty Soesilowati; Agus Sumanto (Economics and Business Journal (ECBIS), 2026)
This study aims to analyze the role of corruption in moderating the influence of Village Funds, Local Own-Source Revenue (PAD), and technology represented by the Electronic-Based Government System (SPBE) index on the number of independent villages in Indonesia from 2023 to 2024. The research was conducted in 34 provinces in Indonesia, except for the provinces of DKI Jakarta, Central Papua, South Papua, and Papua Pegunungan. The study used a panel data regression model with a Fixed Effect Model approach. The results of the study show that: First, Village Funds have a positive and significant effect on increasing the number of independent villages; Second, PAD does not have a significant effect on the number of independent villages, indicating that fiscal independence of villages in Indonesia is still relatively low. Most villages still depend on transfers from the central government; Third, technology, represented by the SPBE index, has a positive and significant effect on the number of independent villages; Fourth, the moderating effect of corruption shows diverse dynamics. Corruption negatively moderates the relationship between Village Funds and independent villages, but conversely positively moderates the relationship between PAD and independent villages. Fifth, the interaction between SPBE and corruption is not proven to be significant, suggesting that the success of digitization in promoting village independence is determined more by the readiness of the technological ecosystem than solely by low levels of corruption.